2014
DOI: 10.1016/j.biomaterials.2014.04.089
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of hepatocellular carcinoma patient-derived xenografts using 89Zr-labeled anti-glypican-3 monoclonal antibody

Abstract: Imaging probes for early detection of hepatocellular carcinoma (HCC) are highly desired to overcome current diagnostic limitations which lead to poor prognosis. The membrane protein glypican-3 (GPC3) is a potential molecular target for early HCC detection as it is over-expressed in >50% of HCCs, and is associated with early hepatocarcinogenesis. We synthesized the positron emission tomography (PET) probe 89Zr-DFO-1G12 by bioconjugating and radiolabeling the anti-GPC3 monoclonal antibody (clone 1G12) with 89Zr,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Yang et al. constructed a PET probe, 89 Zr ‐desferrioxamine‐1G12, and investigated its HCC‐binding capacity; the results showed that 89 Zr ‐desferrioxamine‐1G12 accumulated selectively in subcutaneous HCC and orthotopic xenografts . The results of in vivo studies highlight the probe's potential for clinical translation—for use in early detection of HCC.…”
Section: Diagnostic Value Of Gpc3 In Hccmentioning
confidence: 99%
“…Yang et al. constructed a PET probe, 89 Zr ‐desferrioxamine‐1G12, and investigated its HCC‐binding capacity; the results showed that 89 Zr ‐desferrioxamine‐1G12 accumulated selectively in subcutaneous HCC and orthotopic xenografts . The results of in vivo studies highlight the probe's potential for clinical translation—for use in early detection of HCC.…”
Section: Diagnostic Value Of Gpc3 In Hccmentioning
confidence: 99%
“…In order to target the contrast agents, the composition was linked to a novel HCC biomarker, the heparin sulfate proteoglycan glypican-3 (GPC3), which is highly expressed in most HCC patients' cancer cells, but not in normal adult tissues. [27][28][29][30][31][32][33] Thus, given the HCC-specific nature of GPC3 expression, we hypothesized that ultrasound molecular imaging using GPC3-targeted NBs would allow transfecting of rGO sheets to the HCC cell membrane and highly accurate monitoring of the PTT process in real time. To the best of our knowledge, application of GPC3coated and rGO-loaded NBs as ultrasonic photothermal agent directed at HCC cells has not been reported elsewhere, and is considered innovative.…”
Section: Introductionmentioning
confidence: 99%
“…It is less likely that internalization caused rapid breakdown of antibody with release from tumor, given that very good localization was seen in several patients. Pre-clinical studies have shown a slow rate of internalization of GPC3 targeted with antibody [ 17 , 18 ]. Although we believe that internalizing antibodies are likely to be more successful for imaging when labeled with residualizing radionuclides rather than with non-residualizing halogens such as iodine, because of the eventual release of radioiodine after internalization [ 35 , 36 ], we do note that I-124-labeled antibodies that internalize have been used successfully for tumor imaging [ 6 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other positron emitters have been utilized for antibody labeling, including Ga-68, Cu-64, and Y-86, but these are limited by the short T 1/2 in comparison to the pharmacokinetics of intact antibody [ 10 , 11 ]. Zr-89, a long-lived positron emitter that has been used successfully both clinically [ 4 , 12 16 ] and in pre-clinical testing subsequent to the start of our trial [ 17 , 18 ], could have been a reasonable alternative for radiolabeling. Our choice of I-124 for labeling was justified based on two reasons: (1) concerns that using residualizing radiometals such as Zr-89 would result in higher liver background, as has been found with other radiometals (In-111 and Lu-177), thus lowering tumor-to-normal liver contrast, and (2) the slow internalization rate of GPC3 when targeted by a radiolabeled antibody [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%